Ошибки и коррективная обратная связь: современная теория об ошибках и их исправлении на практических занятиях (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The article deals with updated theory on errors and correction. Error correction is one of the most contentious issues in foreign language teaching profession.